Daily provision of instrumental and emotional support to friends is associated with diurnal cortisol during adolescence. Issue 5 (10th February 2021) - Armstrong‐Carter, Emma; Telzer, Eva H.
Abstract: This study investigates how adolescents' daily prosocial behaviors to friends are related to diurnal cortisol using between‐ and within‐subject analyses. Further, we examine whether role fulfillment (i.e., feeling like a good friend) moderates links between prosocial behaviors and cortisol. Ethnically diverse adolescents ( N  = 370; ages 11–18) reported whether they provided instrumental and emotional support to friends for 5 days, and provided four saliva samples/day for 4 days. On the daily level, providing emotional support predicted lower cortisol awakening response the next day, and providing instrumental assistance to friends was associated with a flatter cortisol slope the same day (a cardiovascular risk factor). Adolescents also provided more emotional support on days they had lower CAR and steeper cortisol slopes. On the average level, providing more instrumental support was associated with steeper cortisol slopes among adolescents who felt high levels of role fulfillment, but not among adolescents who felt low levels of role fulfillment. Providing instrumental support may be physiologically taxing from day to day but, across the long term, linked to lower cardiovascular risk for adolescents who experience helping as highly fulfilling.